Application of a two layer model with the aid of a slope collapse model to the natural landslide dam outburst process - Yoshino, K.; Takahama, J.; Mizuyama, T.; Ogawa, K.; Uchida, T. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"Earthquakes and heavy rainfall result in the formation of landslide dams following a massive collapse or landslide. Landslide dams can result in catastrophic outburst floods or debris flows when the dam breaches with overtopping erosion. Therefore, it is important to determine the discharge rate and area of flooding due to overtopping erosion to mitigate disasters triggered by landslide dams. This study applied a two-layer model that incorporates a slope-collapse model to the erosion process at landslide dams. The two-layer model was proposed by Takahama and deals with the process of deposition-erosion with fully dispersed debris flow and sediment sheet flow. A two-layer model is derived to unify these two kinds of flow. Moreover, Takahama applied this model to a two-dimensional numerical simulation of debris flow, and found that the model can analyze phenomena in which the veloc- ity direction of the upper-layer water ow differs from that of the lower layer sediment-water mixture ow. Furthermore, we introduced the slope-collapse model proposed by Sekine to express gradual collapse of the slope due to erosion in the riverbed. The model shows the process that maintains a constant angle at the side bank. We examined the erosion and deposit process of a landslide dam with a numerical simulation."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">Earthquakes and heavy rainfall result in the formation of landslide dams following a massive collapse or landslide. Landslide dams can result in catastrophic outburst floods or debris flows when the dam breaches with overtopping erosion. Therefore, it is important to determine the discharge rate and area of flooding due to overtopping erosion to mitigate disasters triggered by landslide dams. This study applied a two-layer model that incorporates a slope-collapse model to the erosion process at landslide dams. The two-layer model was proposed by Takahama and deals with the process of deposition-erosion with fully dispersed debris flow and sediment sheet flow. A two-layer model is derived to unify these two kinds of flow. Moreover, Takahama applied this model to a two-dimensional numerical simulation of debris flow, and found that the model can analyze phenomena in which the veloc- ity direction of the upper-layer water ow differs from that of the lower layer sediment-water mixture ow. Furthermore, we introduced the slope-collapse model proposed by Sekine to express gradual collapse of the slope due to erosion in the riverbed. The model shows the process that maintains a constant angle at the side bank. We examined the erosion and deposit process of a landslide dam with a numerical simulation.